Growth and Impact of Bloom’s Taxonomy Applications in Academic Library Research: A Bibliometric Study - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies, 2026)
Bloom’s Taxonomy has become a foundational framework in educational and library contexts, guiding instructional design, assessment, and information literacy programs. Despite its extensive pedagogical application, there is a limited systematic analysis of its growth, impact, and scholarly trends within academic library research. This study aims to examine the growth, patterns, and impact of research on Bloom’s Taxonomy applications in academic libraries using bibliometric analysis. It seeks to identify publication trends, authorship patterns, leading journals, citation impact, country-wise contributions, and thematic focus. Bibliographic data were retrieved from major scholarly databases covering publications from 2000 to 2024. Quantitative bibliometric indicators, including publication count, authorship distribution, citation analysis, and keyword frequency, were employed. Additionally, thematic analysis using Bloom’s cognitive domains was applied to assess the pedagogical focus of the research. The findings reveal a steady growth in publications, with a marked increase after 2015, reflecting heightened attention to outcome-based education and library instruction. Collaborative authorship dominates the field, with a core group of prolific and highly cited authors shaping scholarly discourse. Leading journals such as Journal of Academic Librarianship and College and Research Libraries have served as primary publication outlets. Keyword analysis emphasises the centrality of “Bloom’s Taxonomy,” “Information Literacy,” and “Learning Outcomes.” Country-wise contributions indicate strong leadership from the USA, followed by the UK, Canada, and India. Bloom’s Taxonomy has demonstrated significant scholarly and pedagogical impact in academic library research. The consistent growth in research output, coupled with citation patterns and thematic focus, confirms its role as a robust framework for instructional design, assessment, and learner-centred library education. The study highlights opportunities for further global collaboration and integration with emerging digital learning technologies.
Keywords: Academic Libraries; Bibliometric Analysis; Bloom’s Taxonomy; Information Literacy; Learning Outcomes; Library Instruction